Canones: the art of harmony: the canon tables of the four gospels - Bausi, Alessandro; Reudenbach, Bruno; Wimmer, Hanna (Studies in manuscript cultures, 2020)
Frontmatter --Contents --Canones: The Art of Harmony --Carl Nordenfalk --Do the Eusebian Canon Tables Represent the Closure or the Opening of the Biblical Text? Considering the Case of Codex Fuldensis --Transmission and Transformation of the Eusebian Gospel Apparatus in Greek Medieval Manuscripts --The Eusebian Apparatus in Irish Pocket Gospel Books: Absence, Presence and Addition --An Ethiopian Miniature of the Tempietto in the Metropolitan Museum of Art: Its Relatives and Symbolism --Beyond Eusebius: Prefatory Images and the Early Book --Eusebian Reading and Early Medieval Gospel Illumination --A Tale of Two Tables: Echoes of the Past in the Canons of the Sainte-Croix Gospels --Saxum vivum and lapides viventes: Animated Stone in Medieval Book Illumination --Shifting Frames: The Mutable Iconography of Canon Tables --List of Contributors --Index of Manuscripts